Prof. Dr. Doğan Taner’s Role in The Foundation Years of Hacettepe University Faculty of Medicine and His Perspective on the Medical Education - Fırat, Ayşegül (Acta Medica, 2021)
Prof. Dr. Doğan Taner’s Role in The Foundation Years of Hacettepe University Faculty of Medicine and His Perspective on the Medical Education